Pendidikan Anti Korupsi: Keluarga Sehat, Integritas Terjaga Di Lingkungan Ibu-ibu Dharma Wanita LLDIKTI Wilayah VII Jatim - Suyono; I Wayan Arsana; Budi Santosa; Risma Widia Ramadhanti; Meisin Nabilah (Politeknik Piksi Ganesha Indonesia, 2025)
Research conducted for the implementation of anti-corruption training for women of Dharma Wanita LLDIKTI Region VII East Java regarding education in the family as a strategic social unit to shape values and attitudes in future generations. Anti-corruption education is an important part and the main foundation to foster the values of honesty, rationality, and responsibility in daily life. The purpose of the research is to be able to increase the understanding of mothers about the importance of honesty and instill anti-corruption values in the family sphere. The method used is a collaborative approach through the Community Action Project which involves training, group discussions, and education on anti-corruption values. The results of the study show that there is an increase in the awareness of mothers on the importance of their role in instilling anti-corruption values in children from an early age. The training shows that it is effective in maintaining the integrity of the family and society, where anti-corruption value-based education needs to be implemented properly to create a generation with anti-corruption character.